Implementation of The Independent Curriculum Trough Authentic Learning in Fiqh Subject at Madrasah Tsanawiyah Qita - Shobihatul Fitroh Noviyanti; Ana A’yun Qurrota Amiliya; Shafiyah Amatullah; Malihatul Mu’auwwanah (Pondok pesantren As-salafiyah As-Safi'iyyah, 2025)
This study aims to analyze the implementation of the Independent Curriculum at QITA Junior High School, especially in the Fiqh subject. A qualitative method was employed, utilizing observation, interviews, and documentation involving teachers and the learning process. The findings indicate that QITA School has successfully implemented the Independent Curriculum with authentic, student-centered learning that integrates religious values with technology and science. Project-based activities, such as video lectures, enhance creativity and engagement. Regulated use of cellphones supports focus in learning. The implications suggest that such implementation can serve as a model for other Islamic schools seeking innovative approaches to religious education